The Development of Electronic-based Student Worksheets to Facilitate the Critical Thinking Skills of Tenth Graders - Yanti, Alya Rahma; Mawardi, Ari Cahya (Impulse: Journal of Research and Innovation in Physics Education, 2023)
Smartphones become something familiar to learners. Most learners have smartphones. Learners require guidance to use smartphones for learning. This matter becomes the principle of developing an electronic-based worksheet. Based on the encountered problems especially the materials about renewable energy and critical thinking, the learners needed the development of an electronic-based worksheet to facilitate their cognitive skills within the material of renewable energy.  This research and development, R&D, applied the 4D design, starting from defining, designing, developing, and disseminating. However, this research only lasted until the development stage specifically the limited test. The result showed the category of extremely excellent from the learners. On the other hand, the implementation of the whole aspect was done excellently.